Quantitative characterization of LiFePO4 cathodes reconstructed by FIB/SEM tomography - Ender, Moses Johannes; Joos, Jochen; Carraro, Thomas; Ivers-Tiffée, Ellen (Journal of the Electrochemical Society, 2012)
The three-dimensional microstructures of a lab-scale and a high-power LiFePO4 cathode for lithium-ion cells are analyzed by combined focused ion beam (FIB) / scanning electron microscopy (SEM) tomography. The spatial distributions of (a) carbon black as electronic conductor (b) LiFePO4 as active material and (c) pore volume are reconstructed by appropriate image processing methods. The global threshold segmentation procedure is replaced by a refined local threshold method, which accounts for gradients in luminosity even within very large imaged volumes. The precise analysis of the high-power cathode demands for reconstructing a very large volume of 18.15 × 17.75 × 27.8 μm3, caused by the dual length-scale design of LiFePO4, carbon black and pore phase. The microstructure features, (a) electrochemically active surface area and particle size distribution of LiFePO4, (b) shape and particle size distribution of carbon black and (c) porosity and tortuosity of the pore phase are compared between lab-scale and high-power cathode.